AMH protects the ovary from doxorubicin by regulating cell fate and the response to DNA damage - Ngoc Minh Phuong Nguyen; Eun Mi Chang; Maëva Chauvin; Natalie Sicher; Aki Kashiwagi; Nicholas Nagykery; Christina Chow; Phoebe May; Alana Mermin-Bunnell; Josephine Cleverdon; Thy Duong; Motohiro Kano; et al. (Proceedings of the National Academy of Sciences, 2025)
Anti-Müllerian hormone (AMH) protects the ovarian reserve from chemotherapy, and this effect is most pronounced with Doxorubicin (DOX). However, DOX toxicity and AMH rescue mechanisms in the ovary have remained unclear. Herein, we characterize the consequences of these treatments in ovarian cell types using scRNAseq. DOX-induced DNA damage activates Tp53 class mediators across ovarian cell types. In the mesenchyme, cotreatment with AMH halts theca progenitor differentiation and reduces apoptotic gene expression. In preantral granulosa cells, DOX upregulates the cell cycle inhibitor Cdkn1a and dysregulates Wnt signaling, which are ameliorated by AMH cotreatment. Finally, AMH induces Id3 , a gene involved in DNA repair, which is necessary to prevent the accumulation of DNA lesions marked by γ-H2AX. Altogether these mechanisms of AMH protection contribute to sustained fertility in mice, offering promising broad avenues for fertility preservation in cancer patients undergoing chemotherapy.